Increasing self-efficacy in sea-level athletes racing at altitude - Newell, D. R. (Track Coach, 2014)
The purpose of this study was to investigate whether or not sea-level living and training cross country student-athletes could increase their self-efficacy and confidence lo perform a specific task/performance at moderate altitude; through the use of a psychological skills training program that included goal setting and positive verbal lectures. A modified version of Bandura's Behavioral Model Questionnaire was used as a short-term and long-term goal setting form that could also be used to gather, monitor, and determine changes in the student-athlete's selfefficacy to achieve a specific task/performance at moderate altitude (Individual and Team). A modified version of Vealey's Trait Sport Confidence Inventory (TSCI), and a modified version of Vealey's State Sport Confidence Inventory (SSCI) was used to gather, monitor, and determine changes in the student-athlele's trait and state sport confidence to perform a specific task/performance at moderate altitude. Positive verbal lectures on altitude education and racing tactics were used weekly prior to key workouts and races to improve self-efficacy and trait and state sport confidence.